Three UDP-xylose transporters participate in xylan biosynthesis by conveying cytosolic UDP-xylose into the Golgi lumen in Arabidopsis. (28th December 2017) - Zhao, Xianhai; Liu, Nian; Shang, Na; Zeng, Wei; Ebert, Berit; Rautengarten, Carsten; Zeng, Qing-Yin; Li, Huiling; Chen, Xiaoyang; Beahan, Cherie; Bacic, Antony; Heazlewood, Joshua L; et al.
Abstract : The cytosolic pool of UDP-xylose and its transport into the Golgi lumen play an essential role in xylan and xyloglucan biosynthesis. The equilibrium of these nucleotide sugar pools is controlled by UDP-xylose transporters. Abstract: UDP-xylose (UDP-Xyl) is synthesized by UDP-glucuronic acid decarboxylases, also termed UDP-Xyl synthases (UXSs). The Arabidopsis genome encodes six UXSs, which fall into two groups based upon their subcellular location: the Golgi lumen and the cytosol. The latter group appears to play an important role in xylan biosynthesis. Cytosolic UDP-Xyl is transported into the Golgi lumen by three UDP-Xyl transporters (UXT1, 2, and 3). However, while single mutants affected in the UDP-Xyl transporter 1 (UXT1) showed a substantial reduction in cell wall xylose content, a double mutant affected in UXT2 and UXT3 had no obvious effect on cell wall xylose deposition. This prompted us to further investigate redundancy among the members of the UXT family. Multiple uxt mutants were generated, including a triple mutant, which exhibited collapsed vessels and reduced cell wall thickness in interfascicular fiber cells. Monosaccharide composition, molecular weight, nuclear magnetic resonance, and immunolabeling studies demonstrated that both xylan biosynthesis (content) and fine structure were significantly affected in the uxt triple mutant, leading to phenotypes resembling those of the irx mutants. Pollination was also impaired in the uxt triple mutant, likely due to reduced filament growth and anther dehiscence caused by alterations in the composition of the cell walls. Moreover, analysis of the nucleotide sugar composition of the uxt mutants indicated that nucleotide sugar interconversion is influenced by the cytosolic UDP-Xyl pool within the cell. Taken together, our results underpin the physiological roles of the UXT family in xylan biosynthesis and provide novel insights into the nucleotide sugar metabolism and trafficking in plants.